Habenaria Willd. - Chinchilla Alvarado, Isler Fabián (2022)
The genus Habenaria was named in 1805 by the famous German botanist, dendrologist, and pharmacist Carl Ludwig Willdenow, a professor at the University of Berlin, member of the Berlin Academy of Sciences and director of the Berlin Botanical Garden, one of the founders of dendrology and phytogeography, and a mentor of the young Alexander von Humboldt. The generic name comes from the Latin habena, meaning rein or strap, in reference to the long, narrow segments of the petals and lip, which resemble the “reins of the horse.” Willdenow based the genus on the Habenaria macroceratitis, which grows from Florida (USA) and Mexico through Central America and the Caribbean, to Colombia, Venezuela, and the Guianas in South America.